2015
DOI: 10.1007/s00438-015-1101-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between the methylenetetrahydrofolate reductase c.677C>T polymorphism and bone mineral density: an updated meta-analysis

Abstract: Many studies have reported an association between the methylenetetrahydrofolate reductase (MTHFR) c.677C>T polymorphism and reduced bone mineral density (BMD), but results have been inconsistent. We, therefore, performed a meta-analysis to further explore this association. Twenty-one studies, comprising 33,045 subjects, analyzed the association of MTHFR c.677C>T with femoral neck BMD. Significant association with reduced BMD was observed in Caucasians (recessive model: WMD = -0.004 g/cm(2), 95 % CI -0.008 to -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, oxidative damage and the adverse effects of Hcy on endothelial-derived nitric oxide could increase risk of fracture [182][183][184]. MTHFR polymorphism C667 T could also be involved in the increase of osteoporotic fracture incidence [181], and a recently published meta-analysis showed an association between MTHFR C667 T polymorphism and reduced bone mineral density in the lumbar spine and femoral neck in Caucasians, post-menopausal women, and men, and with total BMD in women [185]. Ahn et al [186] reported an association in 301 postmenopausal women between osteoporotic vertebral compression fractures and MTHFR and TS gene polymorphisms in the 3 -UTR region.…”
Section: Osteoporosismentioning
confidence: 99%
“…Moreover, oxidative damage and the adverse effects of Hcy on endothelial-derived nitric oxide could increase risk of fracture [182][183][184]. MTHFR polymorphism C667 T could also be involved in the increase of osteoporotic fracture incidence [181], and a recently published meta-analysis showed an association between MTHFR C667 T polymorphism and reduced bone mineral density in the lumbar spine and femoral neck in Caucasians, post-menopausal women, and men, and with total BMD in women [185]. Ahn et al [186] reported an association in 301 postmenopausal women between osteoporotic vertebral compression fractures and MTHFR and TS gene polymorphisms in the 3 -UTR region.…”
Section: Osteoporosismentioning
confidence: 99%
“…MTHFR is methylenetetrahydrofolate reductase, which catalyzes the conversion of 5,10-methylenetetrahydrofolate to 5-methyltetrahydrofolate, a cosubstrate for homocysteine remethylation to methionine. Variants within this gene have been associated with BMD ( Li et al., 2016 ). EPHB2 is EPH receptor B2.…”
Section: Resultsmentioning
confidence: 99%
“…According to the meta-analysis, the MTHFR c.677C > T variant was linked to a decreased lumbar spine and femoral neck BMD in Caucasian men and postmenopausal women. This polymorphism was also associated with a reduced total body BMD in women (Li et al 2016 ). In fact, postmenopausal Thai women with the MTHFR 677 CT genotype presented a higher risk of osteopenia than the control group genotype (OR = 5.66; P -value < 0.001) (Tongboonchoo et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%